ASSESSMENT OF PRIMARY AND SECONDARY IMPLANT STABILITY BY RESONANCE FREQUENCY ANALYSIS IN ANTERIOR AND POSTERIOR SEGMENTS OF MAXILLARY EDENTULOUS RIDGES - Denis Baftijari; Alberto Benedetti; Antonio Kirkov; Aleksandar Iliev; leksandar Stamatoski; Florent Baftijari; Elitsa G. Deliverska; Elizabeta Gjorgievska (Peytchinski Publishing, 2018)
Purpose: The aim of this study was to analyze the implant stability quotient (ISQ) results of the resonance frequency (RF) during the first day of surgery and 3 months after dental implant placement in the maxilla. Material and methods: This study was approved by 40 patients with total or partial edentulous maxillary jaws underwent with 85 dental implants. The ISQ values were measured from these 85 implants at baseline and 3 months after placement. Osttell Mentor device was invented to measure the RF value of the implant fixture through the transducer or pin. Measurements were taken 4 times in each direction of the inserted oral dental implant. OPG X-ray images were also obtained to evaluate the bone and neighbouring anatomical structures. Results: The ISQ at baseline had a mean value of 58 (SD 5.91) for all implants placed in anterior and posterior sectors of maxillary ridges. The mean ISQ value on the 3rd month (secondary stability) after placement for all implants was 65 (SD 5.55). An ISQ value ≥65 was observed in 65 implants (78.82%) after 3 months of placement. Differences between primary and secondary mean ISQ values were statistically significant (p < 0.001). The one year cumulative success rate was 98.3% for tested and inserted oral implants. Conclusion: The results of presented study demonstrates and suggests that the influence and reliability of Osstell ISQ values, measured immediately and 3 months after placement it's predictable for the oral implant outcomes, especially analyzing the sensibility of secondary RFA values.